Spatio-temporal variability of land surface temperature estimated from Landsat TM images in dehesa ecosystems: the role of tree cover - Vlassova, Lidia; Rosero Tufiño, Pedro; Montorio Llovería, Raquel (Geographicalia, 2017)
Dehesas are sylvo-agro-pastoral ecosystems with complex mechanisms of carbon and water interchange due to existence of contrasted ecophysiological vegetation layers: tree and grass. One of the key variables in parametrization of energy balance in these systems is Land Surface Temperature(LST). This study analyzes spatio-temporal variability of LST as a function of tree cover in dehesa ecosystem in the northern part of the province of Cáceres. LST is retrieved from a series of 14 Landsat-5 TM images (2009-2011) grouped and analyzed by season (spring, summer and autumn). Tree cover is estimated from the orthophotos and SIOSE data. Spatial distribution of LST is related to the percentage of tree cover in autumn and even more in summer, the moment when mean differences among the lowest and the highest categories established according tree cover percentage (<10% and >60%) achieve 2,5°C.